Physicochemical Evaluation of the Upper Litani River Watershed, Lebanon - Mark Saadeh; Lucy Semerjian; Nabil Amacha (The Scientific World Journal)
This study aims to determine the extent of groundwater damage in the Upper Litani River Basin (ULRB) after years of water mismanagement and overfertilization in what is considered to be Lebanon’s largest fertile area. Physical and chemical samples were collected between 2005 and 2010 and analyzed using “The Standard Methods for the Examination of Water and Wastewater” (APHA, AWWA) in order to determine the extent of this pollution. The parameters included pH, ammonia, nitrate, nitrite, sulfate, phosphate, dissolved oxygen, and total dissolved solids.